Investigating the knowledge and attitude of mothers with teenagers toward human papillomavirus vaccine injection - Leila Shasti; Sayeda Zeinab Hoseinnezhad; Zohre Keshavarz; Maryam Najiabhary; Farangis Habibi; Zeinab Hamzegardeshi (Journal of Education and Health Promotion)
BACKGROUND: Human papillomavirus (HPV) is a large family of viruses and is considered the most common sexually transmitted infection. One of the effective and cost-effective primary prevention methods are vaccines made against the HPV. Considering the significant prevalence of HPV disease and the importance of its prevention, this study was prepared and compiled with the aim of determining the knowledge and attitude of mothers with teenagers toward the injection of the HPV vaccine and its related factors in order to increase the acceptance of this virus vaccination. MATERIALS AND METHODS: The current research is a cross-sectional study (descriptive and analytical) that was conducted in the health and treatment centers of Pakdasht city in the year 2021. The sample size was calculated to be 407 people, which consisted of mothers with teenage girls or boys aged 11–16 years. The tools of data collection were information-demographic-medical form, questionnaire measuring knowledge, and attitude of mothers about HPV. Experiment and data analysis were done with SPSS version 26. Strobe checklist was also used to write the text of the article. RESULT: The average age of mothers was 35.61 (6.11) and the average age of fathers was 41.61 (7.21). Most of the people (49.1%) had one child, and most of the children were girls (57.5%). The average knowledge score was 23.98 ± 3.22, and the average attitude score was 10.04 ± 1.84. The average total score of knowledge and attitude was 34.02 ± 4.12 (at the average level). The results of the Mann–Whitney test indicated that the mean average of knowledge and attitude according to the gender of the child, membership in virtual medical networks, place of residence, income adequacy, history of cervical cancer in the family, history of physical illness in teenagers, and history of genital warts mean (P) < 0.05) were significant. Also, Spearman’s test showed that there is a positive and significant correlation between mothers’ knowledge and attitude toward the HPV vaccine (R = 0.296), which was statistically significant (P < 0.05). CONCLUSION: The results of this study indicate that the acceptance of vaccination by mothers can be related to various factors. Therefore, it is expected that by knowing the factors related to the acceptance rate of mothers, we design support programs in line with increasing the acceptance of mothers to carry out adolescent vaccinations.